Ecological Model of Global Citizenship Education Curriculum in Pesantren-Based Universities - Saifulloh, Ahmad; Utomo, Bambang Setyo; Azizah, Nurul (Newinera Publisher, 2025)
Global Citizenship Education (GCE) has emerged as an important tool to prepare students for addressing the challenges of globalized world. However, Islamic higher education institutions are still struggling in implementing GCE. This study examines the design and implementation of GCE curricula at pesantren-based universities in Indonesia. Utilizing Bronfenbrenner’s Ecological Systems Theory as a framework, the study focuses on how GCE is integrated into the formal, informal, and hidden curricula within pesantren’s unique ecological systems. This research which employs case study design with interactive analysis model finds that both universities participated in this research develop students’ global competencies such as critical thinking, cultural adaptability, and social responsibility. UNIDA employs an integrative approach, embedding GCE across its curriculum, whereas UDN adopts a cross-curricular strategy. Despite strengths in informal and hidden curricula within both universities, challenges remain in transitioning from teacher-centered to student-centered pedagogy in formal learning. This study underscores the moral and humanistic orientation of GCE in pesantren-based universities and sets the groundwork for future research to develop a comprehensive GCE model tailored to residential higher education institutions.